Transradial approach for coronary chronic total occlusion interventions: Insights from a contemporary multicenter registry. Issue 7 (3rd February 2015) - Alaswad, Khaldoon; Menon, Rohan V.; Christopoulos, Georgios; Lombardi, William L.; Karmpaliotis, Dimitri; Grantham, J. Aaron; Marso, Steven P.; Wyman, Michael R.; Pokala, Nagendra R.; Patel, Siddharth M.; Kotsia, Anna P.; Rangan, Bavana V.; et al.
<x xml:space="preserve">Abstract</x> Objectives To examine the impact of transradial access on the procedural outcomes of chronic total occlusion (CTO) percutaneous coronary interventions (PCI). Background The efficacy and safety of transradial access in CTO PCI has received limited study. Methods We compared the technique and outcomes of transradial vs. transfemoral access among 650 CTO PCI cases performed between January 2012 and March 2014 at 6 US centers. Results Most patients were men (87%) with high frequency of diabetes mellitus (42%) and prior coronary artery bypass graft surgery (36%). The CTO target vessel was the right coronary (59%), left anterior descending (20%), or circumflex (17%) artery. TR access was used in 110 (17%) of the 650 cases, as follows: bilateral radial access (63%); bilateral radial access plus unilateral or bilateral femoral access (7%); unilateral radial access plus unilateral or bilateral femoral access (26%); and unilateral radial access (4%). Six and eight French guide catheters were used through the radial and femoral artery, respectively. Compared to transfemoral, transradial cases had similar technical (92.6% vs. 93.0%, P = 0.87) and procedural (91.1% vs. 90.0%, P = 0.95) success and major complication rates (1.7% vs 1.8%, P = 0.99). However, transradial access was associated with higher mean procedure (142 ± 83 vs. 120 ± 60 min, P = 0.008) and fluoroscopy (58 ± 40 vs. 49 ± 31 min, P <0.026) time, and number of crossing approach changes (0.7 ± 1.0 vs. 0.5 ± 0.7, P = 0.008). Conclusion Transradial CTO PCI can be performed with similar success and complication rates with transfemoral CTO PCI, but is associated with longer procedural and fluoroscopy times. © 2015 Wiley Periodicals, Inc.